2013
DOI: 10.1073/pnas.1312477110
|View full text |Cite
|
Sign up to set email alerts
|

Sound response mediated by the TRP channels NOMPC, NANCHUNG, and INACTIVE in chordotonal organs of Drosophila larvae

Abstract: Mechanical stimuli, including tactile and sound signals, convey a variety of information important for animals to navigate the environment and avoid predators. Recent studies have revealed that Drosophila larvae can sense harsh or gentle touch with dendritic arborization (da) neurons in the body wall and can detect vibration with chordotonal organs (Cho). Whether they can also detect and respond to vibration or sound from their predators remains an open question. Here we report that larvae respond to sound of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
161
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(171 citation statements)
references
References 48 publications
9
161
0
1
Order By: Relevance
“…The Drosophila larva has become an important model for studying diverse aspects of physiology and behavior, including metabolism (Palanker et al, 2009), wound healing (Galko and Krasnow, 2004), locomotion and feeding (Schoofs et al, 2014), and sensory perception (Zhang et al, 2013). Studies of any of these processes could benefit from ultrastructural analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The Drosophila larva has become an important model for studying diverse aspects of physiology and behavior, including metabolism (Palanker et al, 2009), wound healing (Galko and Krasnow, 2004), locomotion and feeding (Schoofs et al, 2014), and sensory perception (Zhang et al, 2013). Studies of any of these processes could benefit from ultrastructural analysis.…”
Section: Discussionmentioning
confidence: 99%
“…29) NompC is also essential in the transduction of cuticular deformation by campaniform sensillae, 30) in auditory transduction by Johnston's organ in adult Drosophila 31,32) and in vibration detection by the lateral (pentascolopidial) chordotonal organs in Drosophila larvae. 33) NOMPC is also present in the distal tip of the cilium of leg chordotonal organs, where it is likely to also be involved in sensory transduction for the proprioceptive sense. 34) Because of its widespread importance in sensitive mechanosensory processes of touch, hearing and proprioception and the importance of these senses in social interactions and behavior, NOMPC is likely to be a valid insecticidal target.…”
Section: Trpnmentioning
confidence: 99%
“…As mentioned, it was already well established that class IV Md neurons are crucial in mediating nociception, and it was recently shown that larval chordotonal neurons respond preferentially to vibration signals [15,16] and are tuned to the vibration produced by predatory wasps [16]. The second key contribution of Ohyama et al [17] is to map several new components of the circuit, down to the command neurons that are sufficient to trigger larval rolling.…”
Section: Current Biologymentioning
confidence: 99%
“…Dispatches chordotonal (Cho) neurons [15,16]. The responses to all these specific sensory cues depend not only on the type of neuron, but also on the molecular machineries involved [12,14,16].…”
Section: Current Biologymentioning
confidence: 99%
See 1 more Smart Citation